Gender Dis-Orienting Interpretations at Saqqara, Egypt - Davide Mazzone (Opticon1826, 2009)
Due to its uncommon scenes, the so-called ‘mastaba of the two brothers’, of Nj-Ankh-Khnum and Khnum-Hotep, seems to be one of the most discussed funerary monuments of the necropolis of Saqqara, situated on the west bank of the Nile, 33km south of Cairo. Ever since the unearthing in 1964, and the full publication and restoration in the 1970s (Moussa and Altenmüller 1977), archaeologists have been puzzled by the sentimental images of the two men portrayed in a series of funerary scenes. Some painted reliefs on the walls, particularly at the entrance and on the east wall of the small offering chamber (Moussa and Altenmüller 1977: plates 51, 73, 90, 91), transmit a feeling of ‘exaggerated affection’ between the two individuals (Baines 1985, 479). For the considerate visitors, the reliefs portraying the couple held in the scene of the kiss are truly touching. However, the hypothetical lack of clear indications of the relationship between the two men ‘provides fertile ground for speculation’ (Reeder 2000, 195). For that reason, the monument offers an interesting case of vivid debate about gender studies (Reeder 2000; 2008). Westendorf (1977), but also Reeder in a more recent series of articles (2000; 2008), has already proposed an original interpretation: we are facing here a case (rare) of homosexual relationship in ancient Egypt. In this respect, as a homosexual icon, the tomb is acquiring fame as a popular destination for gay tourists in Egypt (Holland 2006). The idea to which Reeder refers in his papers has obtained the exposure needed to challenge the more ‘conservative’ brothers/twins interpretation (Baines 1985; Parkinson 1995). Were these intimate individuals, ‘superintendents of the royal manicurists’ at the court of the king Nj-Wsr-Ré (Old Kingdom, c. 2494-2345 BC), engaged in a homosexual relationship? To what extent is this suggestion convincing?
Keywords: homosexuality; funerary art